Mechanisms regulating proteostasis are involved in sympatric speciation of the blind mole rat, Spalax galili. Issue 4 (2nd April 2016) - Rodriguez, Karl A.; Li, Kexin; Nevo, Eviatar; Buffenstein, Rochelle
ABSTRACT: Genome-wide analysis demonstrates extensive genomic adaptive complexes involved in sympatric speciation between blind mole rats ( Spalax galili ) in abutting populations living in basalt and chalk soils. Among the gene ontology (GO) enrichment, musculature and metabolism stood out in basalt dwellers while nutrition and neurogenetics were highlighted in chalk residents. Measurements of mechanisms regulating protein homeostasis inspired by these GO terms suggest that at the proteomic level there is also a habitat/soil-type driven divergence with the basalt residents exhibiting higher proteasome activity whereas elevated levels of markers of autophagy are evident in the chalk inhabitants.